Role of targeted therapy in the treatment of HER-2-positive breast cancer brain metastases - G. A. Dashyan; V. F. Semiglazov; P. V. Krivorot’ko; T. Yu. Semiglazova; E. E. Topuzov; R. M. Paltuev; K. Yu. Zernov; V. S. Apollonova; S. S. Ereshchenko; A. V. Petrova; E. K. Zhil’tsova; O. A. Ivanova (Опухоли женской репродуктивной системы, 2016)
Brain metastases are detectable in 25–35 % of patients with progressive HER-2-positve breast cancer. Even after spreading metastases into the brain, chemotherapy in combination with anti-HER- 2 therapy improves survival due to better control of the systemic disease. The paper presents the results of investigations substantiating the use of anti-HER-2 targeting agents, as well as the innovative agent T-DM1 to treat brain metastases.